2018
DOI: 10.4103/jmau.jmau_2_18
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorating effect of sodium selenite on the histological changes and expression of caspase-3 in the testis of monosodium glutamate-treated rats: Light and electron microscopic study

Abstract: Monosodium glutamate (MSG) is a commonly used flavor enhancer that may contribute to male infertility. Sodium selenite is inorganic chemical form of selenium (Se). Se is best known as an antioxidant. This study was designed to investigate the possible ameliorating role of sodium selenite against MSG-induced testicular toxicity and histological changes. Forty male albino rats were allocated into four groups. Control group received distilled water, SE group received sodium selenite (0.25 mg/kg/day) dissolved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 55 publications
13
17
0
Order By: Relevance
“…In the present study, H&E-stained sections of MSG-group revealed many histological changes including disorganized germinal epithelium, a noticeable decrease in the number of spermatogenic cells and absence of sperms in lumina of tubules. Our findings came in harmony with the results of previous studies on MSG-induced testicular toxicity [17,40,41]. The maturation arrest observed in the present study, represented by few number of spermatogenic cells and absence of sperms, was explained by El-Wessemy who correlated this arrest to testosterone inhibition which caused stopping of spermatogenesis [42].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, H&E-stained sections of MSG-group revealed many histological changes including disorganized germinal epithelium, a noticeable decrease in the number of spermatogenic cells and absence of sperms in lumina of tubules. Our findings came in harmony with the results of previous studies on MSG-induced testicular toxicity [17,40,41]. The maturation arrest observed in the present study, represented by few number of spermatogenic cells and absence of sperms, was explained by El-Wessemy who correlated this arrest to testosterone inhibition which caused stopping of spermatogenesis [42].…”
Section: Discussionsupporting
confidence: 92%
“…Also, MSG has toxic direct action on glutamate receptors and transporters that are expressed in epithelial cells of the seminiferous tubules [43]. Wide interstitial spaces filled with acidophilic hyaline material, congested blood vessels and numerous interstitial cells were observed in our study which confirmed other findings [41]. Previous studies attributed wide interstitial spaces to shrinkage of seminiferous tubules and hyperplasia of Leydig cells as a result of endocrine homeostasis disturbance [44].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study shows that the administration of MSG led to significant increases in P53, caspase-3, and apoptotic (Bax) proteins and a substantial reduction in antiapoptotic (Bcl-2) proteins. This was in the same line with [92,93], who explained that glutamate-induced the Ca2 + influx and destruction of the internal mitochondrial membrane potential, resulting in the unregulated mitochondrial permeability of the pores to apoptotic markers [94]. Graviola was found to decrease the higher levels of Bax, caspase 3, and P53 and significantly increase Bcl2 in MSG-treated rats.…”
Section: Discussionsupporting
confidence: 84%
“…Sarhan [15] reported, MSG at a dose of 6 mg.gBW -1 per day for 45 days in male rats increased the production of reactive oxygen species (ROS) which was marked by an increase in MDA levels significantly. In addition, there is damage in the testis in the form of a decrease in the diameter and height of the epithelial layer in the seminiferous tubules.…”
Section: Introduction *mentioning
confidence: 99%